Respuesta :
Since the constant has been moved to the left side, you can move on to the next step which is adding (b/2)² to both sides of the equation.
h² + 14h + (14/2)² = -31 + (14/2)²
Simplify the parenthesis and exponent.
h² + 14h + 7² = -31 + 7²
h² + 14h + 49 = -31 + 49
h² + 14h + 49 = 18
Factor the expression of the left.
(h + 7)(h + 7) = 18
Take the square root of both sides.
√(h + 7)(h + 7) = ± √9 • 2
(h + 7) = ± 3√2
h + 7 = ± 3√2
Subtract 7 from both sides.
You solutions are:
h = -7 + 3√2 → -2.7573 → -2.76
h = -7 - 3√2 → -11.2426 → -11.24
h² + 14h + (14/2)² = -31 + (14/2)²
Simplify the parenthesis and exponent.
h² + 14h + 7² = -31 + 7²
h² + 14h + 49 = -31 + 49
h² + 14h + 49 = 18
Factor the expression of the left.
(h + 7)(h + 7) = 18
Take the square root of both sides.
√(h + 7)(h + 7) = ± √9 • 2
(h + 7) = ± 3√2
h + 7 = ± 3√2
Subtract 7 from both sides.
You solutions are:
h = -7 + 3√2 → -2.7573 → -2.76
h = -7 - 3√2 → -11.2426 → -11.24
Given H^2+14h=-31, let's complete the square of the 1st two terms:
h^2 + 14h + (14/2)^2 = -31 + (14/2)^2
h^2 + 14h + 49 = -31 + 49 = 18
(h+7)^2 = 18
Taking the sqrt of both sides,
h+7 = sqrt (9*2) = 3 sqrt(2)
Solving for h, h= -7 plus or minus 3 sqrt(2) (answer)
h^2 + 14h + (14/2)^2 = -31 + (14/2)^2
h^2 + 14h + 49 = -31 + 49 = 18
(h+7)^2 = 18
Taking the sqrt of both sides,
h+7 = sqrt (9*2) = 3 sqrt(2)
Solving for h, h= -7 plus or minus 3 sqrt(2) (answer)